Unique regulation of the active site of the serine esterase S-formylglutathione hydrolase. - Cummins, I; McAuley, K; Fordham-Skelton, A; Schwoerer, R; Steel, P; Davis, B; Edwards, R (2006)
S-Formylglutathione hydrolases (SFGHs) are highly conserved thioesterases present in prokaryotes and eukaryotes, and form part of the formaldehyde detoxification pathway, as well as functioning as xenobiotic-hydrolysing carboxyesterases. As defined by their sensitivity to covalent modification, SFGHs behave as cysteine hydrolases, being inactivated by thiol alkylating agents, while being insensitive to inhibition by organophosphates such as paraoxon. As such, the enzyme has been classified as an esterase D in animals, plants and microbes. While SFGHs do contain a conserved cysteine residue that has been implicated in catalysis, sequence analysis also reveals the classic catalytic triad of a serine hydrolase. Using a combination of selective protein modification and X-ray crystallography, AtSFGH from Arabidopsis thaliana has been shown to be a serine hydrolase rather than a cysteine hydrolase. Uniquely, the conserved reactive cysteine (Cys59) previously implicated in catalysis lies in close proximity to the serine hydrolase triad, serving a gate-keeping function in comprehensively regulating access to the active site. Thus, any covalent modification of Cys59 inhibited all hydrolase activities of the enzyme. When isolated from Escherichia coli, a major proportion of recombinant AtSFGH was recovered with the Cys59 forming a mixed disulfide with glutathione. Reversible disulfide formation with glutathione could be demonstrated to regulate hydrolase activity in vitro. The importance of Cys59 in regulating AtSFGH in planta was demonstrated in transient expression assays in Arabidopsis protoplasts. As determined by fluorescence microscopy, the Cys59Ser mutant enzyme was shown to rapidly hydrolyse 4-methylumbelliferyl acetate in paraoxon-treated cells, while the native enzyme was found to be inactive. Our results clarify the classification of AtSFGHs as hydrolases and suggest that the regulatory and conserved cysteine provides an unusual redox-sensitive regulation to an enzyme functioning in both primary and xenobiotic metabolism in prokaryotes and eukaryotes.